(In, Er)2O3 Alloys and Photoluminescence of Er3+ at Indirect Excitation via the Crystalline Host. Issue 3 (25th October 2018) - Kalusniak, Sascha; Orphal, Laura; Schäfer, Peter; Kuznetsov, Alexander S.; Benson, Oliver; Sadofev, Sergey
Abstract : (In1− x Er x )2 O3 ternary alloys are grown on A‐plane sapphire wafers by plasma‐assisted molecular beam epitaxy. The layers crystallize in the cubic bixbyite structure with 〈 111 〉 axis aligned parallel to the substrate normal. The d‐spacing of the {111} lattice planes linearly increases with increasing the Er molar fraction in accordance with Vegard's law. Incorporation of Er in the In2 O3 matrix is accompanied by the widening of the optical gap and linear increase of the peak absorption coefficient reaching 380 cm −1 at the telecommunication wavelength of 1.54 µm. The samples exhibit Er 3+ ‐related emission at indirect excitation via the crystalline host at room temperature. Abstract : (In, Er)2 O3 alloys are grown by plasma‐assisted molecular beam epitaxy. Incorporation of Er is accompanied by the widening of the optical gap and increasing of the Er 3+ peak absorption up 380 cm −1 at the wavelength of 1.54 µm. The samples exhibit Er 3+ ‐related photoluminescence at indirect excitation via the (In, Er)2 O3 host at room temperature. Due to the small lattice mismatch of the parent binaries and in conjunction with Sn‐doped In2 O3, the fabrication of multilayer structures comprising plasmonic, dielectric, and light emitting layers is feasible.